The effect of liabilities plan and earnings performance on firm’s worth moderated by independent commissioners - Frans Lengo Boro; Fahreza Eka Yudha; Nuryaman Nuryaman (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Competition in the business world keeps Indonesian economy growing. The aim of study is in order to test correlation between liabilities plan and earnings performance on firm’s worth, as well as moderation by independent commissioners on this correlation. The method is descriptive and verification method. Data collection was carried out by secondary data tracking. The research was conducted with a sample of 39 companies through non-probability sampling methods. Collected data is analyzed using descriptive analysis and verification analysis assisted by Microsoft Office Excel 2016 and Eviews 9 applications. The findings indicated that value of company was not impacted by liabilities plan. Earnings performance has a positive and significant impact on Firm's worth. Independent commissioners have a considerable and beneficial effect on firm’s worth. Independent commissioners are unable to weaken influence of debt policies on firm’s worth. Independent commissioners can enhance impact of earnings performance on firm's worth.